Feature selection method based on grey wolf optimization for coronary artery disease classification - Al-Tashi, Q. (Springer Verlag, 2019)
Cardiovascular disease has been declared as one of the deadly illness that affects humans in the Middle and Old ages across the globe. One of the cardiovascular disease known as Coronary artery, has recorded the highest number of motility rates in the recent years. Machine learning tools have been very effective in investigating the causes of such lethal disease which involve analyzing large amount of dataset. Such datasets might contain redundant and irrelevant features which affect the classification accuracy and processing speed. Hence, applying feature selection technique for the elimination of the said redundant and irrelevant features is necessary. In this paper, a novel wrapper feature selection method is proposed to determine the optimal feature subset for diagnosing coronary artery disease. This proposed method consists of two main stages feature selection and classification. In the first stage, Grey Wolf Optimization (GWO) is used to find the best features in the disease identification dataset. In the second stage, the fitness function of GWO is evaluated using Support Vector Machine classifier (SVM). Cleveland Heart disease dataset is used for performance validation of the proposed method. The experimental results showed that, the proposed GWO-SVM outperforms current existing approaches with an achievement of 89.83 in accuracy, 93 in sensitivity and 91 in specificity rates. Â© Springer Nature Switzerland AG 2019.